Telaah Implikasi Pembedaan Status Kepegawaian PPPK dan Pemenuhan HAM dalam Payung Hukum PPPK di Indonesia - Salwa Husna Sekai Suryawi; Waluyo Waluyo; Asianto Nugroho (Amal Insani Foundation, 2023)
This research is based on the presence of Government Employees with Work Agreements (PPPK) in the horizon of the civil service, who are one of the civil servants besides the State Civil Servants (PNS). PPPK holds the same position as PNS, but in terms of employment status, PPPK has a different employment status. This distinction in work status has effects on everything from the length of the employment contract to the fulfillment of human rights obligations, which are different from other civil servants as stated in the regulatory framework related to PPPK in Indonesia. This research aims to identify any regulations related to PPPK that identify status and positional differentiation, which would have negative effects on PPPK, as well as to ascertain whether Indonesian regulations or legal frameworks pertaining to PPPK are consistent with the principles of human rights. This study is a normative research using statute and conceptual approaches related to PPPK regulations, as well as the theory of legal certainty by Gustav Radbruch, and examines several legal sources. Therefore, the discussion and research results will focus more on the differences in employment status and the fulfillment of rights for PPPK within the legal framework governing PPPK in Indonesia.